The developmental origins of Notch-driven intrahepatic bile duct disorders - Anabel Martinez Lyons; Luke Boulter (The Company of Biologists, 2021)
The Notch signaling pathway is an evolutionarily conserved mechanism of cell-cell communication that mediates cellular proliferation, cell fate specification, and maintenance of stem and progenitor cell populations. In the vertebrate liver, an absence of Notch signaling results in failure to form bile ducts, a complex tubular network that radiates throughout the liver, which, in healthy individuals, transports bile from the liver into the bowel. Loss of a functional biliary network through congenital malformations during development results in cholestasis and necessitates liver transplantation. Here, we examine to what extent Notch signaling is necessary throughout embryonic life to initiate the proliferation and specification of biliary cells and concentrate on the animal and human models that have been used to define how perturbations in this signaling pathway result in developmental liver disorders.